2018
DOI: 10.1101/373464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subjective perceptual experience tracks the neural signature of sensory evidence accumulation during decision formation

Abstract: OBJECTIVE:The aim of this study was to assess whether inclusion of hands-on molecular laboratories improved student outcomes on molecular questions during the final course examination.METHOD: CLS faculty evaluated student learning by written examination of lecture and laboratory content. Researchers performed two-sample t-tests to establish if significant differences existed in molecular questions scores achieved by students exposed to virtual and hands-on exercises.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Previous research has also shown that the amplitude of the CPP captures the strength of a perceptual experience (Tagliabue et al, 2019), consistent with the notion that it indexes the strength of accumulated evidence in favour of a particular perceptual decision (Murphy et al, 2015;O'Connell et al, 2012;Twomey et al, 2015). We therefore next tested whether CPP 28 amplitude in our paradigm varied with subjective ratings of confidence, visibility, or attention.…”
Section: The Cpp Positively Correlates With Subjective Confidence And...supporting
confidence: 71%
See 1 more Smart Citation
“…Previous research has also shown that the amplitude of the CPP captures the strength of a perceptual experience (Tagliabue et al, 2019), consistent with the notion that it indexes the strength of accumulated evidence in favour of a particular perceptual decision (Murphy et al, 2015;O'Connell et al, 2012;Twomey et al, 2015). We therefore next tested whether CPP 28 amplitude in our paradigm varied with subjective ratings of confidence, visibility, or attention.…”
Section: The Cpp Positively Correlates With Subjective Confidence And...supporting
confidence: 71%
“…In the case of the linear relationship between alpha power and attention, we were able to test for this tripartite relationship using our mediation analysis, and demonstrate that a significant mediation pathway exists linking these three outcomes. It is important to note that as variations in spontaneous alpha power partially determined CPP amplitude, our observation adds to a growing literature that the CPP represents the accumulation of decision likelihood based on internal states, which include the subjective certainty of a decision (Gherman & Philiastides, 2015;Rangelov & Mattingley, 2020;Tagliabue et al, 2019), as opposed to a pure index of physical sensory evidence (e.g. O'Connell et al, 2012).…”
Section: Prestimulus Alpha Power and Subjective Reportsmentioning
confidence: 67%
“…The broad fronto-central distribution of the late decoding pattern (350–500 ms) that we have linked to decision confidence in the current study (for similar findings, see Gherman and Philiastides, 2015, 2018) is reminiscent of similar signals observed in previous EEG studies related to several cognitive processes associated with challenging perceptual decisions. For example, a similar broad central parietal positivity (CPP) has been shown to scale with the amount of evidence accumulated toward a decision (O’Connell et al, 2012; Kelly and O’Connell, 2013), subjective ratings of stimulus visibility during perceptual decisions (Del Cul et al, 2007; Tagliabue et al, 2018), and improvements in postsensory processing due to category-selective perceptual learning (Diaz et al, 2017). It may be that the signals that we measure on the scalp with EEG reflect a mixture of decision processes, including evidence accumulation, confidence computation, and error monitoring (Boldt and Yeung, 2015), with further studies required to disentangle and pinpoint the neural signatures of each process.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were carried out on the data from 34 individuals (15 males, 19 females, mean age: 24, min = 17, max = 33). 20 participated in a line bisection experiment and 14 participated in a luminance discrimination experiment Tagliabue et al, 2018). All participants gave written informed consent and were financially compensated for their time.…”
Section: Participantsmentioning
confidence: 99%